SIKAP PEDAGANG KAKI LIMA TERHADAP LINGKUNGAN DI KOTA DENPASAR - Pariartha, I Wayan Wana (Bumi Lestari Journal of Environment; Vol 11 No 1 (2011), 2011)
Human with his environment is an ecosystem, i.e. as an integrated order and holistic system among all comprehensive environmental elements that affect each other. Therefore the attitude of the human in this study is sidewalk vendors on the environment need to be investigated. The attitude of the trash is one of the indicators used in this study. The principal issues in this study is whether it is true that the educational background, age and income affect the manner and attitude of street vendors in the trash? The aim of this study is, to know the effect of educational background, age and attitude of street vendor’s income to dispose of waste. This study was a survey which was held in four Districts in Denpasar. Samples were collected by quota sampling system, i.e. of 75 persons in each district so that the number of respondents as many as 300 people. Data was collected by using questionnaires with was proceeded by field observation. The collected data was analyzed descriptively with the help of quantitative data in the form of cross table. The study found that, factor income each person in relation to attitudes toward issues of environmental cleanliness, have a positive correlation, It just revealed at the answers most of the respondent of street vendors in the West Denpasar District. Meanwhile relations with the educational level of attitude towards the environment and community interests, seems also to have no positive correlation, unless a majority of respondents in North Denpasar District showed a positive relationship, where the higher education tends respondents attained greater levels of concern for the level of cleanliness environment. On the other hand also showed that age, as independent variables that affect the attitudes of respondents to the interests of view of environmental cleanliness has a positive correlation at the North Denpasar District and South Denpasar District, In the contrary a negative correlation occurred in the of East Denpasar District and West Denpasar District.
Keywords: environment; vendors; ecosystem; trash